Pharmacological options of osteoarthritis therapy - Tuchocka-Piotrowska, Aleksandra (Przewodnik Lekarza/Guide for GPs, 2007)
Osteoarthritis (OA) – the most frequent among various rheumatic entities – is a chronic and irreversible disease. Its aetiopathogenesis is a very complex process in which genetic background, transcription factors and proinflammatory cytokines play a part, acting in cooperation with immunocompetent cells to have an impact on the structure and function of the joint compounds. The most important part of OA management, being in the 1st place and initiating complex care of the patients, regardless of the disease location, is non-pharmacological treatment. The majority of drugs recommended have only symptomatic effects with minimal influence on the progression rate and degenerative changes resulting in pain, impaired function, worsening quality of life and finally disability.